Pengaruh Kompetensi Manajerial dan Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru - Lili Sartika; Tri Widayatsih; Andi Rahman (Journal on Education, 2023)
This study aims to identify and describe: 1). the influence of the principal's managerial competence on teacher performance; 2) the influence of the principal's leadership style on teacher performance, 3) the effect of managerial competence and the leadership style of the principal on the performance of vocational school teachers in East Baturaja District. This study uses a quantitative descriptive method. The population and sample in this study were 144 teachers at SMK East Baturaja, with the sample technique used was total sampling. The data collection technique used is a questionnaire. Data were analyzed using simple linear and multiple linear regression formulas using the SPSS (Statistical Product and Services Solution) program. The results of the study show that: 1) There is a significant influence on the managerial competence of school principals on the performance of vocational school teachers in East Baturaja District; 2) There is a significant influence of the principal's leadership style on the performance of SMK teachers in East Baturaja District; 3) There is a significant influence of managerial competence and leadership style of the principal on the performance of vocational school teachers in East Baturaja District. This can be seen from the results of the F test which shows a significance value of 0.000 <0.005. The influence of managerial competence and the principal's leadership style on the performance of SMK teachers in East Baturaja District is 38.1%, the remaining 61.9% is influenced by other factors.